Analytical assessment of the outdoor performance and efficiency of grid-tied photovoltaic system under hot dry climate in the south of Algeria. (1st September 2018) - Necaibia, Ammar; Bouraiou, Ahmed; Ziane, Abderrezzaq; Sahouane, Nordine; Hassani, Samir; Mostefaoui, Mohammed; Dabou, Rachid; Mouhadjer, Samir
Highlights: The assessment of 2.5 kWp photovoltaic (PV) system installed in the south of Algeria. The most appropriate and relevant performance indices were used to analyze the PV system performances. PV system performance depend on both irradiance and module temperature. Performance analysis exhibit high losses in PV system due to environmental factors. Abstract: A detailed assessment analysis of 2.5 kWp photovoltaic (PV) system located in southern Algeria (Latitude 27.88 °N, Longitude −0.27 °E, Altitude 262 m) has been carried out in this paper in order to support the growth of grid-tied photovoltaic power plant implementation in the Saharan environment. The achievement of this analysis has been done by performing an accurate evaluation of the different impacts of the environment parameters on the operating performance of the grid-tied PV system. The data set covers 12 operating months and has been collected by our team from the Research Unit on Renewable Energy (URER-MS). The collected experimental data reveal that the environmental parameters variation has direct effect on the performance of both energy conversion efficiency and system losses. The grid was supplied with a power of 4322.65 kWh during the year 2015, where the annual average temperature was 28.30 °C. An important variation in performance parameters have been observed for different months. The yield values of max/min monthly average daily reference, array and final were; 7.68/5.7 kW h/kWp/day, 6.07/4.24 kW h/kWp/day and 5.75/3.98 kW h/kWp/day, respectively. The PV module, inverter and overall system efficiency reached; 14.19/11.10%, 95.34/93.94% and 13.53/10.50%, respectively. The experimental results indicate that the performance ratio (PR) varies from 66.66% to 85.93% and the annual average capacity factor was 7.91%.